Genki Japanese readers Box 1 genki tadoku bukkusu : shokyū Nihongo yomi mono - Banno, Eri; Ikeda, Yoko; Shinagawa, Chikako; Sakai, Mieko (the Japan Times Publishing, 2023)
"GENKI Japanese Readers is an elementary extensive reading resource. Its 46 readings cover a broad range of material, including funny stories, scary tales, Japanese folk tales, and introductions to places in Japan. The grammar and vocabulary correspond to the content of the popular GENKI elementary Japanese series. Each reader is written in simple Japanese so that learners can enjoy reading them without relying on a dictionary" ; "The grammar items and vocabulary of two GENKI Japanese Readers titles correspond to those of a single GENKI textbook lessons."--Site internet de l'éditeur
in japanischer Schrift